2014
DOI: 10.1007/978-3-662-45504-3_31
|View full text |Cite
|
Sign up to set email alerts
|

On the Diversity Order of UW-OFDM

Abstract: International audienceUnique word (UW) OFDM is a multicarrier technique that follows a different approach than standard multicarrier techniques like cyclic prefix (CP) OFDM. It has been reported that UW-OFDM outperforms CP-OFDM in the sense that it performs better in fading channels [1, 2], and it has much lower out-of-band radiation [3] compared to CP-OFDM. However, a theoretical analysis of the error rate performance of UW-OFDM was never addressed in the literature. In this paper, we derive analytical expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In [1], it is shown that UW-OFDM outperforms cyclic prefix (CP-) OFDM with respect to the bit error rate in fading channels. This is confirmed in [2] where a theoretical analysis of the error rate performance shows that UW-OFDM is always able to achieve full diversity, whereas in CP-OFDM only a diversity one is obtained unless precoding is used. Further, it is shown in [3] that UW-OFDM has…”
Section: Uw-ofdmmentioning
confidence: 64%
See 2 more Smart Citations
“…In [1], it is shown that UW-OFDM outperforms cyclic prefix (CP-) OFDM with respect to the bit error rate in fading channels. This is confirmed in [2] where a theoretical analysis of the error rate performance shows that UW-OFDM is always able to achieve full diversity, whereas in CP-OFDM only a diversity one is obtained unless precoding is used. Further, it is shown in [3] that UW-OFDM has…”
Section: Uw-ofdmmentioning
confidence: 64%
“…To satisfy the constraints on the signal shape, the system parameters specify both the mapping matrix B and the null-space matrix U. The designer only has the freedom to select the linear combination matrix W. In [2], it is shown that, in order to achieve full diversity, the code generator matrix must be full rank. Hence also W should be full rank.…”
Section: Euclidean Distance At the Transmittermentioning
confidence: 99%
See 1 more Smart Citation